Roughness of Fuzzy Ideals in Left Almost Semigroups (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we introduce the concept of rough fuzzy bi-ideals and rough fuzzy interior ideals in LA-semigroups. We prove that the lower and the upper aproximation of a fuzzy bi-ideal (fuzzy interior ideal) is a fuzzy bi-ideal (fuzzy interior ideal).2010 AMS Classification 03E72, 20M10.